1989
DOI: 10.1002/ca.980020204
|View full text |Cite
|
Sign up to set email alerts
|

Clinical anatomy of the peritoneal mesothelium: A review

Abstract: This paper reviews the structure, function, and clinical significance of peritoneal mesothelium, once thought to be a passive membrane, but now known to play an active role in exchanges between the peritoneal cavity and the blood. The advent of continuous ambulatory peritoneal analysis (CAPD) has revived interest in the peritoneum, whose ultrastructure is much changed by CAPD. Studies of the healing of mesothelium have shown that the new mesothelium develops from subperitoneal perivascular connective tissue ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
0
1
0
4
Order By: Relevance
“…In addition, mesothelial cells play an important role in solute transport, immune surveillance, inflammation, and wound healing. These functions of mesothelial cells are important also in the context of PD and have thoroughly been discussed in several excellent reviews [1,2,3,4,5,6,7]. Numerous studies have shown that both exposure to PD fluid components and the presence of PD-associated inflammation alter the function of mesothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mesothelial cells play an important role in solute transport, immune surveillance, inflammation, and wound healing. These functions of mesothelial cells are important also in the context of PD and have thoroughly been discussed in several excellent reviews [1,2,3,4,5,6,7]. Numerous studies have shown that both exposure to PD fluid components and the presence of PD-associated inflammation alter the function of mesothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ο τραυματισμός του περιτοναίου, ανεξάρτητα της αιτίας, οδηγεί σε παραγωγή ινικού εξιδρώματος προκαλώντας την προσκόλληση των παρακείμενων επιφανειών με αποτέλεσμα τον σχηματισμό μετεγχειρητικών συμφύσεων [24] .…”
Section: ιστορικη αναδρομηunclassified
“…Η ινωδολυτική δραστηριότητα συγκεκριμένων μεσοθηλιακών κυττάρων, τους επιτρέπει να διεισδύσουν και να λύσουν τις ινικές συμφύσεις πριν η ινοπλασία οδηγήσει στον σχηματισμό μόνιμων ινώδων συμφύσεων [24] .…”
Section: ιστορικη αναδρομηunclassified
See 1 more Smart Citation
“…ηα επφκελα ρξφληα δηάθνξνη εξεπλεηέο ππνζηήξημαλ πσο νη ζπκθχζεηο ήηαλ απνηέιεζκα επνχισζεο κέζσ ίλσζεο θαη θιεγκνλήο ηνπ πεξηηνλαίνπ θαη ην 1923 δεκνζηεχζεθε απφ ηνπο Williamson θαη Mann ε πξψηε πεηξακαηηθή κειέηε γηα ηελ πξφιεςε ηνπ ζρεκαηηζκνχ ζπκθχζεσλ κε ηε ρξήζε ελφο κείγκαηνο γέιεο αθαθίαο[137]. Σν 1955 ν Hartwell ζεψξεζε πσο ηα κεζνζειηαθά θχηηαξα πξνιακβάλνπλ ηηο ζπκθχζεηο ζπλδπάδνληαο ηελ ηλσδνιπηηθή ηνπο ηθαλφηεηα κε ηελ επηζειηαθή ιεηηνπξγία ηνπο[132]. Ο Myllarmiemi ην 1967 ππνζηήξημε πσο ε ρεηξνπξγηθή θαη ε βαθηεξηαθή πξνζβνιή είλαη γεγνλφηα πξσηαξρηθήο ζεκαζίαο ζηελ αλάπηπμε ησλ ζπκθχζεσλ, ππνδεηθλχνληαο έηζη φηη ε παξνπζία ελφο μέλνπ ζψκαηνο κπνξεί λα εκπνδίζεη ηελ απνξξφθεζε ηεο ηληθήο θαη λα επηηξέςεη ηελ εηζβνιή ησλ ηλνβιαζηψλ πνπ ζηε ζπλέρεηα ζα παξαγάγνπλ κηα ηλψδε ζχκθπζε[138].…”
unclassified